Effect of Stall Strip Position, Size and Geometry on the Lift Coefficient of NACA 001 Aerofoil - Wee, Tee; A. N., Oumer; Ahmmad, Shukrie; Azizuddin, Abdul Aziz; Baheta, Aklilu (EDP Sciences, 2017)
This study aims to determine the optimum position and geometry of stall strips (SS) to control sudden fall of lift in wind turbine blades. The type of airfoil used in this study is NACA 0015 with 150 mm of chord length. Total of five positions, two geometries and three sizes of SS configurations are simulated by using Ansys Fluent software. For position configuration, SS of size 2 mm is placed on the apex (POS-1), and on the upper and lower surfaces at distance of 0.65 mm (POS-4 and POS-2 respectively), and 2.45 mm (POS-5 and POS-3), respectively, from the leading edge. The shapes tested are dome and equilateral triangle. The results show that the addition of SS as a method of controlling sudden loss of lift decreases the maximum lift coefficient. Attachment of SS at the lower surface of the airfoil did not bring any significant effect to the lift and stall characteristics; while for the upper surface it reduces the sudden fall of lift but at the cost of big reduction in maximum lift coefficient. The optimum position and geometry of SS are POS-1 and triangle shape. Increasing in size of SS shows positive effect in control stalling effect.